Effect of Chinese Herbal Medicines on Hearing Loss Risk in Rheumatoid Arthritis Patients: Retrospective Claims Analysis - Li, Hsin-Hua; Livneh, Hanoch; Chen, Wei-Jen; Fan, Wen-Lin; Lu, Ming-Chi; Guo, How-Ran; Tsai, Tzung-Yi (Frontiers in Medicine, 2021)
Objectives: Patients with rheumatoid arthritis (RA) are at higher risk of extra-articular manifestations, especially hearing loss (HL). Although Chinese herbal medicines (CHM) are proven safe and effective treatments for inflammatory conditions, the effect of CHM use on HL in RA patients is unknown. This cohort study aims to determine the relationship between CHM use and the subsequent risk of HL among RA patients. Methods: From health insurance claims data in Taiwan, a total of 6905 persons aged 20–80 years with newly-diagnosed RA in 2000–2009 were identified. Of these, we recruited 2765 CHM users and 2765 non-CHM users who were randomly selected using propensity scores. Both cohorts were followed up until the end of 2012 to estimate the incidence of HL. Cox proportional hazards regression was used to estimate the adjusted hazard ratio (HR) for CHM use. Results: The incidence of HL was lower in the CHM users than in the comparison cohort (8.06 vs. 10.54/1000 person-years, respectively) (adjusted HR, 0.77; 95% CI, 0.63–0.94). Those who received CHM for more than 2 years had the greatest benefit against the onset of HL, with over 50% risk reduction. Prescriptions of Hai Piao Xiao, Yan Hu Suo, San-qi, Huang Qin, Dang Shen, Jia-Wei-Xiao-Yao-San, Shu-Jing-Huo-Xue-Tang, and Dang-gui-nian-tong-tang were found to be associated with a reduced risk of HL. Conclusions: Our findings suggest that adding CHM to conventional therapy may lessen the subsequent risk of HL in RA patients. Prospective randomized trials are recommended to further clarify whether the association revealed in this study supports such a causal relationship.